Optimizing Leader Uniqueness: A Practice-Oriented Approach - Kerns, Charles D. (Journal of Leadership, Accountability and Ethics, 2020)
Leaders have a unique profile of relevant resources to draw upon when facing different situations at work. They can optimize value-added contributions and achieve desired impacts in these situations by using a systematic approach. A practice-oriented approach is offered to help leaders optimize their uniqueness in the many situations they encounter to enhance outcomes, such as performance and well-being. After presenting an Optimizing Leader Cycle and some benefits associated with this process, a seven-step process for applying this approach is provided. A real-world application of the approach with an executive is also presented. Some challenges are also offered including having leaders consider a broader array of stakeholders when considering and measuring impacts.